Influência da competição escolar sobre a eficiência das escolas públicas de ensino fundamental brasileiras - Santos, Yuri Dantas dos (2019)
In line with the studies of economics of education focused on the analysis of competition in schools, this research aimed to verify the influence of school competition on the efficiency of public elementary schools in Brazil. The assumption was that school competition has a predominantly positive influence on the efficiency of Brazilian public elementary schools. In procedural terms, we took as unit of analysis, in each municipality, the set of schools with characteristics previously established regarding the school system (state or municipal) and the offer of years of elementary school (all, only the initial or only the endings). An efficiency index was constructed based on the sequential product-oriented DEA VCR methodology. Competition indices were constructed, which, together with control variables, appeared as independent variables in the econometric model applied to the samples using quantile regression and having as a dependent variable the constructed efficiency index. The data collected refer to the years 2007, 2009, 2011, 2013 and 2015. Three types of competition were analyzed: horizontal (between all schools), private (from private schools) and vertical (between state and municipal schools). Horizontal competition influenced predominantly negatively, and positively influenced in some situations. Evidence indicates that the size of the school system in one location seems to positively influence the efficiency of its schools. In turn, competition from private school enrollment negatively influenced the efficiency of public schools. However, the presence of private schools had a positive influence. Regarding vertical competition between state and municipal schools, the results were quite heterogeneous, but there was a predominance of positive influence with room for negative results. Finally, it can be concluded that the thesis is partially met, as it is confirmed in the aspect of vertical competition, however, there is no predominance of positive influence of horizontal and private competition, in which there is preponderance of negative influence. However, there is evidence of positive long-term influence and improvement in negative indicators depending on managerial changes that make public schools more attractive and competitive.